FEATURES OF THE INSTANTANEOUS FREQUENCY ESTIMATION ALGORITHM WITH PRE-FILTERING - Omelchuk, I.; Chyrka, Y. (Science-based technologies, 2013)
Instantaneous frequency is one of the basic signal parameters which provides important information about the time-varying spectral changes in non-stationary signals. Features of the harmonic signal frequency estimation algorithm in different signal and interference situations are researched. Research methodology is a statistical modeling. Appearance of an additional harmonic considerably worsen precision of estimation because the algorithm does not have any filtering properties. For linear frequency deviation estimation approximately equals middle between initial and final frequencies in the window. Frequency estimation of a noise process, that is formed by 2nd order filters, is almost proportional to central or cut-off frequency. There is optimal formative filter frequency for different filter parameters and estimation conditions. Reasonability of using pre-filtering in order to improve estimation precision is proved. Identified positive effect of mixture pre-filtering is also useful for estimation of frequency of periodic non-harmonic signals with higher harmonics. A great feature of the algorithm is a accurate estimation at intervals equal to a period of the signal, which brings us to the actual instantaneous frequency and provides the opportunity to observe its trend over time. Distorted factors cause significant worsening of frequency estimation precision. It can be improved by pre-filtering. The 2nd order filter using is reasonable only in case of weak a priori ambiguity, in other cases the 1st order filter is more preferable.